Environnement et économie : une relation équivoque - Olivier Boiral (VertigO, 2004)
The reduction of the environmental impacts may involves considerable investments for industrial companies. Confronted, on the one hand, to lawful or societal pressures to foster the adoption of effective systems of pollution reduction and, on the other hand, to economic constraints which limit the non-productive investments, these companies often have a very limited freedom of action. The economic implications of the environmental actions seem all the more difficult to apprehend that the studies on this issue lead to contradictory results. The objective of this paper is to expose the salient debates on the relation between environment and economy by underscoring the ambiguity and circumstantial character of this relation. The complexity of economics’ consequences resulting from environmental actions tends to call into question the simplistic opposition between the "win-win" and "win-loose" hypotheses which dominates the debates over this issue.